2019
DOI: 10.1007/s12639-019-01160-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and antiparasitic effects of garlic–arteether combination via nitric oxide pathway in Plasmodium berghei-infected mice

Abstract: Many reports indicate medicinal value of garlic (Allium sativum), a popular herbal medicine used worldwide, and its therapeutic effect against several diseases. Earlier studies in our laboratory have shown a potential therapeutic role of garlic-artemisinin combination in mice infected with Plasmodium berghei. A single dose of a, barteether with three oral doses of garlic provides almost 95% protection. The present study aims to understand the mode of action of this combination. We have documented the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…typhi, E. coli, and P. aeruginosa. Moreover, Vathsala and Murthy [138] revealed the potent immunomodulatory and anti-plasmodial effect of garlic-artemether combination treatment. They reported that this combined therapy may have a potential role in reducing organ injury and protecting against Plasmodium species by affecting NO production, suggesting novel treatment options against malaria [138,139].…”
Section: Combination Therapy With Other Drugsmentioning
confidence: 99%
“…typhi, E. coli, and P. aeruginosa. Moreover, Vathsala and Murthy [138] revealed the potent immunomodulatory and anti-plasmodial effect of garlic-artemether combination treatment. They reported that this combined therapy may have a potential role in reducing organ injury and protecting against Plasmodium species by affecting NO production, suggesting novel treatment options against malaria [138,139].…”
Section: Combination Therapy With Other Drugsmentioning
confidence: 99%
“…It works by modulation of immunoglobulin production, cytokinin secretion, macrophage activation, and phagocytosis ( Arreola et al, 2015 ). Several studies reported the immunomodulatory and antiviral effects of garlic and its components ( Prajapati et al, 2021 ; Vathsala and Murthy, 2020 ). Some researchers used the molecular docking method and investigated that alliin may be a functional inhibitor of SARS-COV-2 as compared to remdesivir, chloroquine, and ritonavir ( Cheng and Li, 2020 ).…”
Section: Application Potential Of Recommended Treatment To Fight Sars...mentioning
confidence: 99%
“…Garlic ( Allium sativum L.) possesses many beneficial and pharmacological properties in traditional and modern medicine, such as anticancer, antioxidant, antidiabetic, immunomodulatory, antithrombotic, and antimicrobial characteristics [ 20 , 21 ]. It has also anti-parasitic activity against Blastocystis spp., Cryptosporidium parvum , Giardia lamblia , Entamoeba histolytica , Leishmania tropica , L. major , Plasmodium spp., Trypanosoma spp., and Toxoplasma gondii [ 22 28 ]. The therapeutic properties of garlic are owed to the presence of the most bioactive and potent components, allicin and thiosulfate (sulfur-containing compounds) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%